Application of an integral formula to CR-submanifolds of complex hyperbolic space - Jin Suk Pak; Hyang Sook Kim (International Journal of Mathematics and Mathematical Sciences)
The purpose of this paper is to study n-dimensional compact CR-submanifolds of complex hyperbolic space CH(n+p)/2, and especially to characterize geodesic hypersphere in CH(n+1)/2 by an integral formula.